Boxing related muscle fatigue rate of boxers using various sizes of gloves - Chentanez, T.; Kaimuk, P.; Teppanich, S.; Sidhilawa, S.; Damrongpipatkul, P. (Journal of Sports Science Technology, 2005)
The objectives of this study were to investigate and to compare the effects of various size of gloves on boxing-elated muscle fatigue in 10 high experience boxers (HB), 10 medium experience boxers (MB) and 10 non-boxers (NB). Each group of subjects had similar age (mean 16.1+0.84) and had a dominant right hand. Physical fitness test, such as measurements of volumes of arm and leg, percentage of body fat, trunk flexibility, strength of arm and leg and maximum oxygen consumption (VO2max) were performed. Then, a punching test such as force, frequency, and velocity of punching were measured every 15 seconds of continuous punching for 3 minutes. The force, frequency and velocity data of punching were established by an impact force-measuring device and a 2-dimension-motion analysis system. This system was utilized with a camera operating at 50 frames per second. This study determined direct jab punching only. The punching trials were conducted at the shoulder height level of each subject. One way ANOVA was used to analyze the data. The results showed that: 1) The force, frequency, and peak velocity of punching with various gloves (6, 10, 12 and 18 ounces) in all groups of subjects were not significantly different (p<0.05). The frequency of punching among HB, MB and NB were not significantly different in all sizes of gloves (p<0.05). The results suggest that various sizes of gloves shows no difference on muscle fatigue, so it is reasonable that the Boxing Sports Act B.E 2543 encourage young boxers to use bigger gloves instead of small gloves. Since sizes of gloves (6-18 OZs) does not significantly affect the rate of muscle fatigue in the same individual of boxers and general people. The various sizes of gloves in this study may be not a cause of disadvantage of guard drop. If boxers want to have a advantage in competition, they should train to improve physical fitness. The results indicate that boxers should not be anxious about size of gloves since boxers and opponents must use the same size of gloves.